Is Ant Colony System better than FFD for VM placement in a heterogeneous cluster? - Lee, Seungjun; Jeong, Minjoong; Oh, Sangyoon (Proceedings - 2022 IEEE International Conference on Cloud Engineering, IC2E 2022, 2022)
First fit decreasing (FFD) is the most popular heuristic for virtual machine (VM) placement problems. However, FFD does not perform as much in a heterogeneous cluster environment. Moreover, FFD and other heuristics, such as best fit decreasing (BFD), are limited to handle the VM placement problem effectively when multiple resources are considered together. In this study, we analyze the reason why the ant colony system performs better than FFD for VM placement in a heterogeneous cluster. We verified our logical observations through experimental comparisons with other heuristics.
Keywords: Ant's colony system; Best fit decreasing; Cloud-computing; Cluster environments; Experimental comparison; First fit; Heterogeneous clusters; Multiple resources; Placement problems; Virtual machine placements; ant colony system; cloud computing; VM placement